2017
DOI: 10.1186/s12885-017-3898-9
|View full text |Cite
|
Sign up to set email alerts
|

Acacia hydaspica ethyl acetate extract protects against cisplatin-induced DNA damage, oxidative stress and testicular injuries in adult male rats

Abstract: BackgroundCisplatin (CP), an effective anticancer agent, carries the risk of impairing testicular function leading to infertility. The present study aimed at evaluating the protective effect of A. hydaspica ethyl acetate extract (AHE) against CP-induced oxidative stress and testicular injuries in rats.MethodsRats were divided into six groups (n = 6). Group I (control), group II (CP single dose on day 16). Group III received AHE for 21 days. Group IV (CP + AHE; post- treatment group). Group V (AHE + CP; pre-tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
53
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(60 citation statements)
references
References 62 publications
3
53
0
Order By: Relevance
“…We found a CP-mediated decrease in peripheral blood testosterone concentration, likely resulting in a decrease in testosterone concentration in testes, which is fundamentally consistent with previous reports [43,44,53]. It is now accepted that Leydig cells produce testosterone in response to LH and that testosterone acts as a paracrine factor that diffuses into the seminiferous tubules and is required for maintaining spermatogenesis [54].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…We found a CP-mediated decrease in peripheral blood testosterone concentration, likely resulting in a decrease in testosterone concentration in testes, which is fundamentally consistent with previous reports [43,44,53]. It is now accepted that Leydig cells produce testosterone in response to LH and that testosterone acts as a paracrine factor that diffuses into the seminiferous tubules and is required for maintaining spermatogenesis [54].…”
Section: Discussionsupporting
confidence: 92%
“…As such, MDA is used as an indirect indicator of ROS based on the high reactivity and short half-life of ROS making it difficult to quantify [41,42]. Our findings were substantially consistent with previous reports showing that CP treatment causes adverse effects in the testis by inducing oxidative stress and apoptosis [43][44][45][46][47][48][49].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Chromosomal abnormalities in spermatozoa and temporary or permanent azoospermia are associated side effects of CP treatment. These side effects are attributed to oxidative and nitrosative damage generated by CP [ 7 ]. Physiological and biochemical disturbance is caused by redox imbalance and increase in lipid peroxidation lead to germ cell apoptosis [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The previous studies reported that the DNA damage is firmly linked to teratogenicity ( Yang et al, 2014 ; Si et al, 2017 ; Wani et al, 2017 ) and reproductive toxicity ( Lin et al, 2014 ; Yang et al, 2014 ; Afsar et al, 2017 ; Adana et al, 2018 ). QdNOs, acting as an inhibitor of DNA synthesis, induced genotoxicity in the bacteria and mammalian cells ( Cheng et al, 2015 ; Liu et al, 2016 , 2017a ; Wang et al, 2016a ), suggesting that DNA damage may involve in the teratogenicity and reproductive toxicity mediated by MEQ.…”
Section: Discussionmentioning
confidence: 99%